WUJUD CINTA ALAM DALAM PUISI REMAJA KALIMANTAN TIMUR (THE FORM OF LOVE OF NATURE IN POEMS MADE BY ADOLESCENTS OF EAST KALIMANTAN) - Dwi Hariyanto (Balai Bahasa Sulawesi Utara, 2016)
The purpose of the study is to describe the form of love of nature in poems made by adolescents of East Kalimantan. The poems themed nature life made by adolescents are interesting to analyze. The approach of semiotic by doing the heuristic and hermeneutic reading is used to reveal meaning in the poems. Human beings take part in natural disaster. Illegal logging, mining, and forestry take part also in damaging the nature.